Effect of postbiotic Lactiplantibacillus plantarum LRCC5282 on obesity improvement by modulation of the gut microbiome - Ahyoung Lim; Jihye Baek; YoHan Nam; Seokmin Yoon; Jong-Hwa Kim; Jungki Kwak; Gyeong-hwon Lee; Wonyong Kim (Journal of Functional Foods)
This study aimed to evaluate the ameliorating effects of Lactiplantibacillus plantarum LRCC5282 (5282-P) postbiotic on obesity. Treatment with 5282-P decreased the ratio of Firmicutes/Bacteroidetes, increased the abundance of obesity regulation-associated genera, including Bacteroides, and elevated the production of short-chain fatty acids. These microbiome alterations correlated with reductions in adipose tissue weight, improvements in serum lipid profiles, and alleviation of obesity symptoms, including body weight and BMI. Additionally, the mRNA expression levels of adipogenesis-related genes, including leptin, PPAR/γ, SREBPα1, and CEBP/α, were significantly downregulated. These findings suggest that 5282-P enhances metabolic health and improves obesity by promoting a diverse and balanced gut microbiome, making it a promising therapeutic candidate for obesity treatment.